Luminescence properties of Ca₃Ga₂Ge₄O₁₄ crystals - Kostyk, L.; Tsvetkova, O.; Stryganyuk, G. (Functional Materials, 2008)
The spectral and kinetic luminescence characteristics of undoped Ca₃Ga₂Ge₄O₁₄ single crystals have been studied using synchrotron irradiation with 4-30 eV energy, X-ray and optical irradiation (N₂ laser) in 10-300 K temperature range. It is established that the undoped crystals show an intrinsic luminescence consisting of three elementary emission bands peaked at 355, 400, and near 500 nm. The UV emission bands (355 and 400 nm) are effectively excited in exciton absorption and band-to-band regions while the 500 nm emission can be excited in the crystal transparency region. Possible nature of intrinsic luminescence bands in Ca₃Ga₂Ge₄O₁₄ crystals is discussed.